East African Community Annual Report 2014 - 2015 - EAC (EAC, 2016)
The EAC Annual Report 2014/15 has further demonstrated good progress towards the attainment of the EAC integration agenda as stipulated along the four stages of integration, namely Custom Union, Common Market, Monetary Union, and ultimately Political Federation. The implementation of the Single Custom Territory with a pilot phase along the Northern and Central corridors has shown substantial improvement in the turn-around of time for trucks from ports to land-locked Partner States. The region has further consolidated its foundation for a seamless Eat African Community single market, following continued improvement in infrastructure development, especially with the establishment One-Stop-Border Posts for ease movement of goods and services cross-border. This good progress is being further enhanced in the wake of the ongoing negotiations of the COMESA-EAC-SADC Tripartite Free Trade Area (TFTA) that will see widened trade area for increased economies of scale.
Pages: 65, with col. maps, photos, tables, graphs,.
Keywords: Regional development; Economic development